Photo-Induced Dipole Relaxation Current in Natural Amethyst - Russo, Fabricio Trombini [UNESP]; Fernandes Scalvi, Rosa Maria [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Goncalves Vismara, Marcus Vinicius [UNESP] (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2012)
Thermally stimulated depolarization current (TSDC) measurements were carried out for SiO2 in the amethyst form, aiming to investigate the relationship of observed current with relaxation phenomena related to quartz impurities. In addition to TSDC conventional dark procedure, photo-induced TSDC was also carried out, where the exciting light came from an Ar+ laser, tuned either at 488 nm or at 541 nm. X-ray diffraction and optical absorption measurements were used as complement for the interpretation of TSDC data. Optical absorption data, mainly in the range 400-700 nm, allow identifying the characteristic bands of amethyst as well as to relate them with TSDC and photo-induced TSDC data, leading to a relationship between absorption bands and light irradiation with selected wavelengths. These results allow determining how the formation of a TSDC band in the range 220-260 K, is affected by the light absorption, modifying the formation and the dipole orientation distribution in the samples. Results also help the verification of defects formed by Fe3+ or Fe4+ ions in the amethyst structure, as well as suggest that these defects, besides the participation in the amethyst structure as color centers, also play a role in the formation of TSDC bands, contributing for the observed effect of monochromatic light irradiation on these bands.
Keywords: relaxation current; amethyst; dipoles; TSDC